Maternal thrombophilia as a predictor of the onset of obstetric complications and perinatal losses in women with loss of pregnancy, depending on body weight - Ю. М. Дука (Publishing House TRILIST, 2018)
The article gives a scientific and practical justification for the timely detection of maternal thrombophilia at the stage of pregnancy planning taking into account the phenotype of a woman. The aim of the study was to analyze the structure of the revealed gene polymorphisms and their effect on the course of the gestational process and the hemostasis system in pregnant women, depending on the phenotype. Clinical groups were 175 pregnant women with different body weight (120 women with overweight and obesity and 55 pregnant women with normal body weight). The average age of pregnant women in Group I was 30.9 ± 0.4 years, in Group II - 30.3 ± 0.6 years, the average gestational age at the time of registration was 9.39 ± 0.59 and 8.42 ± 0.69 weeks respectively. The influence of intergenic interactions of genes-candidates of thrombophilia and the disturbance of folate metabolism on the occurrence of obstetric complications and perinatal losses in these women was assessed. The mechanisms of development of obstetric complications are clarified depending on the body weight taking into account their genetic determinancy. In particular, carriers of thrombophilia genes in women with miscarriage in 100% of cases, regardless of body weight, have been identified. As the author of the article points out, obesity during pregnancy can cause serious complications for the mother and fetus. Therefore, studies on maternal thrombophilia should be conducted at the pregravidel stage in order to conduct timely pathogenetically based treatment with emphasis on therapy in the fertile cycle, which will improve perinatal outcomes in such women.